Intervensi Pemerintah terhadap Harga Gabah - Astrin, Lily; Wahyudi, Amin (LPPM Institut Nasional Laa Roiba Bogor, 2024)
Basically, the government and private sector have an important role in realizing economic conditions in a country. The problem in the market is the market mechanism and all its problems, therefore, to correct failures and overcome these problems, the government must play a role in ensuring efficiency, equality and stability. The aim of this research is to explain how the government intervenes in the mechanisms of problems that occur in the market in accordance with sharia guidelines in order to achieve good muamalah relations. Government intervention in the market can be carried out if the government finds evidence that market traders are committing acts of ihtikar towards their goods/products and there is a monopoly in the market. This research uses qualitative research methods by collecting data through literature studies from relevant sources. From the research, it can be concluded that the government's intervention in dealing with the problem of increasing grain prices includes: Determining restrictions related to purchasing prices by the National Food Agency (Bapanas), government supervision/controlling can increase its supervision of the grain market to prevent monopolistic practices or unfair price manipulation. fair, carrying out the Cheap Food Movement (GPM), preparing CBP stocks in Bulog, diversifying consumption, and finally by socializing the public to shop wisely.